(3YeGO GdQVG HHjGf COH GdbVGs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3GdMeO ddg Ydi dWag ai bVGFg hGdTcQ dg Ydi fYeg hBdGFg hGdUdGI hGdSdGe Ydi CTQa Ndbg SjOfG eMeO hBdg hUMHg hCUajGFg s
(3BNQgG (B:s
(3Je cJGH GdbVG HMeO Gddg JYGdiq s
(3Vef eLehY , JQJjHgG (B: 1s
(3GdcJGH GdCUdi GdeNJUQ Yfg(B: (3COH GdbVGA dTQa GdOjf YjSi GdZRis
(3GdfSNI HgG MhGTs
(3GdfSNI efbhdI Yf fSNI HNW GdeDdas
(3Ydi dhMI GdYfhGf agQSJ HYfGhjf QSGFd GdeLehYs
(3hYdjg Jedc s
(3bQf GdfSN (B:s
Keywords: (3Gdabg GdTGaYjs